Exploitation of novel local isolates of bacillus subtilis for surfactin yield and isoforms production investigation - Mohammed Abdel-Hafiz Faisal Shannaq
Surfactin production genetic locus (sfp) is responsible for the ability of Bacillus subtilis to produce surfactin which is a lipopeptide biosurfactant. This study describesthe utilization of Polymerase Chain Reaction (PCR) of the sfp gene as a method for identifying B. subtilis species which able to produce surfactin. Three isolates were selected based on the APi 50 CH/B, haemolytic test, and drop collapse assay. These three isolates were tentatively named as B. subtilis MSH1, B. subtilis MSH2 and B. subtilis MSH3. The phylogenetic analysis of these isolates based on comparisons of 16S rDNA sequences, revealed that the strains were closely related to B. subtilis. The identification of surfactin production was determined based on PCR screening of the sfp gene. We carried out High Performance liquid Chromatography (HPLC) analysis for surfactin identification and quantification and to ensure that the PCR provided accurate results. The three isolates yielded surfactin and a good correlation was observed between PCR and HPLC analysis. Liquid Chromatography-Mass Spectrometry (LC-MS) analysis was utilized to determine molecular mass and structure for each surfactin isoforms of B. subtilis MSH1, MSH2, MSH3 and compared to surfactin standard. The three local isolates of B. subtilis produced series of surfactin isoforms, which have similarity with surfactin standard isoforms. The antibacterial activity of surfactin produced by local isolates was of B. subtilis studied by determination of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The antibacterial activity of surfactin was effective in all tested pH levels (5-9). The increase in the membrane permeability was evidenced by the increased in the retention of crystal violet dye, and the leakage of cellular membrane which confirmed the ability of surfactin to rupture the membrane cell of pathogenic bacteria. Antibacterial activities of surfactin produced by local isolates of B. subtilis show good potential to be utilized for commercial antibiotic formulation in medical and pharmaceutical purposes.